2002
DOI: 10.1128/jcm.40.3.1037-1043.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay Based on Soluble Promastigote Antigen Detects Immunoglobulin M (IgM) and IgG Antibodies in Sera from Cases of Visceral and Cutaneous Leishmaniasis

Abstract: Leishmaniasis causes significant morbidity and mortality in areas where it is endemic. In areas where it is nonendemic, global travel and increased incidence of the disease in human immunodeficiency virus and intravenous-drug user populations are also causes for concern. The unavailability of rapid and reliable tests for diagnosis of the various leishmaniases makes patient management difficult. We have developed an enzymelinked immunosorbent assay (ELISA) that can detect immunoglobulin M (IgM) and IgG antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 25 publications
5
59
1
1
Order By: Relevance
“…Indeed, our findings of a 37.5% positivity of ESA with CL and 13.3% with the MCL cases (Table 1) do not agree with those of other authors who have reported 80-92.3% and 71% positive rates when CL samples were assayed with ESA isolated from L. (L.) mexicana and L. (V.) braziliensis, respectively. 13,15 In contrast, similar positivity rates (62.5% for CL and 73.3% for MCL) were observed in our study when Leishmania spp. PRO was used (Table 1).…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Indeed, our findings of a 37.5% positivity of ESA with CL and 13.3% with the MCL cases (Table 1) do not agree with those of other authors who have reported 80-92.3% and 71% positive rates when CL samples were assayed with ESA isolated from L. (L.) mexicana and L. (V.) braziliensis, respectively. 13,15 In contrast, similar positivity rates (62.5% for CL and 73.3% for MCL) were observed in our study when Leishmania spp. PRO was used (Table 1).…”
Section: Discussioncontrasting
confidence: 49%
“…have been a target of interest for decades and have been identified as potential candidates for vaccines, 32 they have not been extensively explored for the diagnosis of leishmaniasis. 5,6,12,13,15 In this report, we present new data suggesting that ESAs isolated from three different species of Leishmania (from the most prevalent species in the Americas) L.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…DiVerent reports documented parasitemia in asymptomatic L. infantum-seropositive blood donors [12,13]. Several hypotheses may be proposed to explain our diVerent results: (i) the screened sample is not wide enough although it is similar to that studied by other authors in the Mediterranean area [12,13]; (ii) the antibody titer may be so low that the tests used are not able to detect it; the global sensitivity of the tests used is reported to range from 95% to 100% in an immunocompetent host [19,20], but asymptomatic subjects show a low humoral immunoresponse so that their antibody levels are under the cut-oV; (iii) ELISA and IFAT are rapid and not very expensive techniques, but they are less sensitive than western blotting, which may give positive results even if classical serological tests are negative [13].…”
Section: Discussionmentioning
confidence: 76%